Cold War (Post-)Truth Regimes: Radio Free Europe between “States of Affairs” and the Epistemology of Hope and Fear - Grutza, Anna (Stan Rzeczy, 2019)
In accord with recent scholarly appeals, this article advocates a certain intellectual tolerance and modesty in regard to the juxtaposition of conflicting or even supposedly rival approaches to questions of epistemology and truth. By rejecting the idea of a fixed epistemological standpoint and by moving the reader along a multiplicity of frames and truth situations, the author argues that if the post-truth problematic can teach us anything new about truth, it is the necessity to (re-)acknowledge that there is no omniscient position for the scholar and that none of our scholarly approaches taken separately enable us to grasp the totality. Hence, truth is investigated in this article as a variable shaping and being shaped by a highly dynamic and uncertain social reality – a reality that is neither constituted of “hard facts” nor of a “soft relativism” alone. From a consideration of the selected Cold War context and the laboratory-like setting of the American broadcaster Radio Free Europe, it can be concluded that a new media-archaeology of the fact requires not only a revision of our understanding of truth but of agency, rationality, and objectivity as well.